O paradoxo da atuação do Supremo TribunalFederal em direito à saude: uma descrição sistêmico-pragmática (Luhmann - Peirce) num diálogo com Marcelo Neves - Lima, Fernando Rister de Sousa (2013)
The Brazilian Federal Constitution of 1988 guaranteed to all citizens the right to health. Nevertheless, the Brazilian government inability to solidify this right fostered a huge amount of legal actions precisely to pursuit social effectiveness. All over the world, this interventionist conduct was labeled as juridical activism. In Brazil, this issue gained unimaginable proportions and has set the judiciary in the center of the discussion stage about Public Policies. And the Brazilian Supreme Court (STF Supremo Tribunal Federal), as guardian of the Federal Constitution and as the top one in the structure of that power, arises as key of this new institutional design of the Principle of Separation of Powers. In that context, the research has as its aim to identify if the STF performance on the right to health results in effectiveness or in symbolism. It was made by a theoretical research and an empirical investigation. The collect of data was centered in theoretical sociologist, with respective prominence given to the Niklas Luhmann´s Theory of Systems, which was used in the identification of legal rationality, social inclusion, complexity, contingence, justice, and the roles of Courts, the Legal and the Political Systems. In the theoretical reference, the conceptualization of the expression: symbolic is extremely rich. To a point that routinely semantic confusion is found; to avoid it, this work embraces the thesis developed by Marcelo Neves in his book: A Constitucionalização Simbólica (The Symbolic Constitutionalization), in which he develops a debate about the symbolism of constitutional norms. For the empirical research, by the methods of research, a documental investigation was made, collected from Brazilian Supreme Court´s leading cases. The study of these sentences was sponsored by the Pragmatic of Charles Sander Pierce. In effect, the research result arranged a paradox. It was found that the Brazilian Supreme Court, in a point of view restricted to the litigants, searches for an illusory effectiveness of the right to health, which is symbolic, inasmuch as the judge from a rationality exclusive adjudicatory, denying to see the issue, therefore, as an distributive issue, as a matter of distribution of wealth, which, in a macro perspective, causes the risk of corruption in the political system for forcing the public administration to distribute a wealth that, sometimes, does not even exist, as well as excluding most of the population, that does not have access to this Court or that indirectly are strained considering the diverged resources from the public health to accomplish its decisions